Examination the role of technical information in the development of nursing education for the Faculty of Nursing at the University of Baghdad - Abbas, ali (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): The study aims at examining the role of technical information used in nursing education, such as "the Internet, e-mail services, video, audio conferencing and other "in the College of Nursing at the University of Baghdad. Methodology: A descriptive and analytical study which was using the examination approach was conducted on a non-probability sample (purposive sample) of (42) members of the faculty of the College of Nursing at the University of Baghdad. A questionnaire was constructed for the purpose of the study. It was consisted of two parts; the first part which included the demographic characteristics of faculty members (such as age, sex, qualification, scientific title, and the scientific department in college) and the second part includes (22) question about the technical information used in nursing education, Where it was built through the review of the literature related to technical information used in education. Data were collected through a self- administration method, from 4 th to 30th September, 2011. Data were analyzed through use of descriptive analysis (frequencies and percentages), and inferential statistical measures which include the (ANOVA). Results: The results of the study indicated that the majority of faculty members are encouraged to use various technical information in education nursing. Conclusion: The study concluded that the high qualification of faculty members led to a high familiarity with technical information and its importance in nursing education. Recommendations: The study recommend the need to develop a database on the use of technical information in the college as well as for the other Nursing colleges universities in Iraq to facilitate the process of identifying needs, planning services for information systems and the optimal allocation of resources for technical information in nursing education.